The ANDEEP Tanaidacea (Crustacea: Peracarida) revisited III: the family Akanthophoreidae - Larsen, Kim; Araújo-Silva, Catarina L. (Zootaxa, 2014)
A restricted phylogenetic analysis is conducted to test if the family Akanthophoreidae is monophyletic. The family was found to be monophyletic with a Bremer support of 11 and is redefined to include the genera Akanthophoreus, Chauliopleona, Mimicarhaphura, Parakanthophoreus gen. nov., Paraleptognathia, Stenotanais, and Tumidochelia, while Gejavis is removed. Akanthophoreus and Paraleptognathia are redefined and now consist of only four and two species respectively. The remaining species previously assigned to these genera are transferred to a new genus Parakanthophoreus. A key to the genera of the family is presented. Two new species of Chauliopleona, C. ciimari and C. andeepi, and one of Parakanthophoreus, P. greenwichius, are described from the ANDEEP I–III and ANDEEP-SYSTCO material.